P85 Human mesenchymal stem cells bind preferentially to injured liver in a β1-integrin and CD44 dependent manner. (6th September 2011) - Aldridge, V; Davies, N; Youster, J; Kavanagh, D; Kalia, N; Lalor, P; Frampton, J; Newsome, P
Abstract : Introduction: Human bone-marrow mesenchymal stem cells (hMSCs) are multipotent cells which have been considered in liver repair due to their immunomodulatory properties. However, they have also been implicated in liver fibrogenesis. These differing actions may reflect the existence of different functional sub-sets of hMSCs or differing environmental cues. Understanding the mechanisms governing the entry and retention of hMSCs into liver would allow this to be modified for clinical benefit in disease settings. Aim: To determine the mechanisms underpinning the adhesion and engraftment of human MSCs into injured liver. Method: Flow cytometric analysis of hMSCs was performed to determine the expression of adhesion molecules corresponding to up-regulated ligands in injured liver. Adhesion of hMSCs to normal and injured liver tissue, human hepatic sinusoidal endothelium (HSEC) and extracellular matrices (VCAM-1, fibronectin and hyaluronan) was undertaken in vitro using static and physiologically relevant modified-flow assays. Fluorescently-labelled hMSCs were infused via the portal vein into mice injured with chronic CCl4 to determine engraftment. To define the molecular mechanisms underpinning hMSC interactions neutralising antibodies were utilised in these assays. Results: hMSCs expressed high levels of β1 -integrin and CD44. Adhesion of hMSCs was greatest on diseased human liver compared to normal liver. Neutralising antibodies against β1 -integrin, CD44 and VCAM-1 reduced binding of hMSCs to diseased liver by 34%, 35% and 40% respectively (p<0.05). hMSCs were seen to fast-roll at 500 μm/s, firmly adhere and transmigrate across HSEC. Rolling was completely abolished by β1 -integrin blockade on both HSEC and VCAM-1. Firm adhesion to HSEC was reduced by blockade of β1 -integrin (55%, p=0.02) and CD44 (51%, p=0.04). To determine which ligands on HSEC mediate hMSC binding we studied the ligands in isolation. HSEC express VCAM-1, fibronectin and hyaluronan, all of which supported firm adhesion of hMSCs under modified flow. β1 -integrin blockade reduced adhesion to VCAM-1 (66%, p=0.001) and Fibronectin (29%, p=0.007), while CD44 blockade reduced adhesion to fibronectin (18%, p=0.02) and hyaluronan (43%, p=0.04). Neutralising antibodies to the β1 -integrin subunit and CD44 reduced hepatic engraftment of hMSCs in chronically injured mice, confirming the data obtained in vitro. Conclusion: hMSCs bind preferentially to injured liver and undergo rolling and firm adhesion, which is differentially regulated. β1 -integrin/VCAM-1 interactions regulate rolling while β1 -integrin/CD44 interactions with fibronectin and hyaluronan regulate adhesion.